2018
DOI: 10.1080/02670844.2018.1467143
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature erosion behaviour of plasma-sprayed NiCrBSi–graphite coatings

Abstract: Plasma-sprayed NiCrBSi-graphite coatings have been subjected to solid particle erosion at elevated temperatures. The work reports the erosion resistance of NiCrBSi coatings with 4, 6 and 8 wt-% addition of graphite and optimum graphite content for erosion resistance. The coatings were analyzed using optical microscopy, XRD and scanning electron microscopy. Testing was carried out using air-jet erosion test rig, at an impact velocity of 70 m s−1 and at 45°and 90°angles with sand flow rate of 1 g min−1 at RT, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Cr 3 C 2 addition in NiCrBSi powder produced excellent wear resistance coating and bond strength [12,13]. Plasma-sprayed NiCrBSi powder with 4% graphite addition improved the erosion resistance and microhardness [14]. An abrasive, adhesive, and oxidative wear mechanism exists for HVOF-sprayed composite coating of nickel-based powder and WC-Co [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cr 3 C 2 addition in NiCrBSi powder produced excellent wear resistance coating and bond strength [12,13]. Plasma-sprayed NiCrBSi powder with 4% graphite addition improved the erosion resistance and microhardness [14]. An abrasive, adhesive, and oxidative wear mechanism exists for HVOF-sprayed composite coating of nickel-based powder and WC-Co [15].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the addition of Y 2 O 3 increased the hardness of 1048HV to 1154HV due to the increased density which subsequently improved the slurry erosion performance. Anand and Natarajan used plasma spray method to apply graphite mixed NiCrBSi coating on 304 stainless steel [59]. Up to 4% of graphite addition, hardness, and erosion performance were improved.…”
Section: Surface Modificationsmentioning
confidence: 99%
“…Also, it is known for producing dense coatings with low oxide formation. The APS deposited NiCrBSi-graphite coatings show the minor effect on the erosion behaviour up to 650 °C [11]. The laser remelting composite coatings of NiCrBSi and WC on stainless steel shows the enhanced sliding wear performance up to 600 °C [19].…”
Section: Introductionmentioning
confidence: 97%
“…In some of the research, the NiCrBSi composite coating developed by different processes for high-temperature conditions. The process like laser remelting [6,7], laser cladding [8], pack cementation method [9], plasma spraying [10][11][12], HVOF [13][14][15][16] used for the deposition of the coating. The high-velocity oxy-fuel (HVOF) and atmospheric plasma spray (APS) processes are the extensively used thermal spraying methods for the NiCrBSi powder [17,18].…”
Section: Introductionmentioning
confidence: 99%